1998
DOI: 10.1096/fasebj.12.15.1651
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione is implied in the control of 7‐ketocholesterol‐induced apoptosis, which is associated with radical oxygen species production

Abstract: In a number of experimental systems, inhibition of apoptosis by antioxidants has led to the production of radical oxygen species (ROS) in certain apoptotic forms of cell death. Since antioxidant therapies can reduce vascular dysfunctions in hypercholesterolemic patients who frequently have increased plasma levels of oxysterols constituting potent inducers of apoptosis, we speculate that oxysterol-induced apoptosis could involve oxidative stress. Here, we tested the protective effects of the aminothiols glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
128
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 195 publications
(145 citation statements)
references
References 82 publications
(102 reference statements)
16
128
0
1
Order By: Relevance
“…In vitro, under treatment with 7-ketocholesterol, 7ß-hydroxycholesterol, cholesterol-5ß,6ß-epoxide, cholesterol-5α,6α-epoxide, and 25-hydroxycholesterol, important oxidative processes, sometimes associated with a complex mode of cell death with some of the characteristics of apoptosis, have also been described on various cell types (15,27,32). Thus, on 7-ketocholesteroltreated U937 cells, an abrupt drop in reduced glutathione associated with an increased production of ROS preceding caspase activation has been reported (46). In human aortic smooth muscle cells, 7-ketocholesterol also induces oxidative stress associated with apoptotic events, and it has been demonstrated that this specific effect of 7-ketocholesterol is mediated by a robust upregulation (3-fold from the basal level) of Nox-4, an ROS-generating NAD(P)H oxidase homologue (32).…”
Section: Oxysterols: Potent Pro-oxidative Moleculesmentioning
confidence: 95%
“…In vitro, under treatment with 7-ketocholesterol, 7ß-hydroxycholesterol, cholesterol-5ß,6ß-epoxide, cholesterol-5α,6α-epoxide, and 25-hydroxycholesterol, important oxidative processes, sometimes associated with a complex mode of cell death with some of the characteristics of apoptosis, have also been described on various cell types (15,27,32). Thus, on 7-ketocholesteroltreated U937 cells, an abrupt drop in reduced glutathione associated with an increased production of ROS preceding caspase activation has been reported (46). In human aortic smooth muscle cells, 7-ketocholesterol also induces oxidative stress associated with apoptotic events, and it has been demonstrated that this specific effect of 7-ketocholesterol is mediated by a robust upregulation (3-fold from the basal level) of Nox-4, an ROS-generating NAD(P)H oxidase homologue (32).…”
Section: Oxysterols: Potent Pro-oxidative Moleculesmentioning
confidence: 95%
“…For all experiments, a stock solution of 7KC was prepared extemporaneously at a concentration of 800 g/ml as previously described (36). To obtain the initial solution, 800 g of 7KC was dissolved in 50 l of absolute ethanol, 950 l of culture medium were added, and the solution was sonicated.…”
Section: Cells and Cell Treatmentmentioning
confidence: 99%
“…Apoptotic cells were characterized by nuclear condensation of chromatin and/or nuclear fragmentation (36). Hoechst 33342 was prepared in distilled water at 1 mg/ml and added to culture medium at a final concentration of 10 g/ml.…”
Section: Nuclear Staining With Hoechst 33342mentioning
confidence: 99%
See 1 more Smart Citation
“…For all experiments, a stock solution of 7KC was prepared at a concentration of 800 lg/ml as previously described (27). To obtain the initial solution, 800 lg of 7KC were dissolved in 50 ll of absolute ethanol, 950 ll of culture medium were added, and the suspension was sonicated.…”
Section: Cells and Treatmentsmentioning
confidence: 99%